Clinical and genomic delineation of the new proximal 19p13.3 microduplication syndrome. Issue 1 (5th October 2022) - Jouret, Guillaume; Egloff, Matthieu; Landais, Emilie; Tassy, Olivier; Giuliano, Fabienne; Karmous‐Benailly, Houda; Coutton, Charles; Satre, Véronique; Devillard, Françoise; Dieterich, Klaus; Vieville, Gaëlle; Kuentz, Paul; et al.
Abstract: A small but growing body of scientific literature is emerging about clinical findings in patients with 19p13.3 microdeletion or duplication. Recently, a proximal 19p13.3 microduplication syndrome was described, associated with growth delay, microcephaly, psychomotor delay and dysmorphic features. The aim of our study was to better characterize the syndrome associated with duplications in the proximal 19p13.3 region (prox 19p13.3 dup), and to propose a comprehensive analysis of the underlying genomic mechanism. We report the largest cohort of patients with prox 19p13.3 dup through a collaborative study. We collected 24 new patients with terminal or interstitial 19p13.3 duplication characterized by array‐based Comparative Genomic Hybridization (aCGH). We performed mapping, phenotype–genotype correlations analysis, critical region delineation and explored three‐dimensional chromatin interactions by analyzing Topologically Associating Domains (TADs). We define a new 377 kb critical region (CR 1) in chr19: 3, 116, 922–3, 494, 377, GRCh37, different from the previously described critical region (CR 2). The new 377 kb CR 1 includes a TAD boundary and two enhancers whose common target is PIAS4 . We hypothesize that duplications of CR 1 are responsible for tridimensional structural abnormalities by TAD disruption and misregulation of genes essentials for the control of head circumference during development, by breaking down the interactions between enhancers and the corresponding targeted gene.